ANALISIS GAYA BAHASA DALAM LIRIK LAGU “CINTA LUAR BIASA” ANDMESH KAMELANG - Nanda Siti Fadilah Ramdan; Aliyya Humaira (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2022)
Destination from study this is for describe style language and meaning which contained on Andmesh . album Love Extraordinary lyrics Kamaleng. Study this is study qualitative with approach descriptive qualitative. Technique collection data in study this is analysis data is identification data, classification data, analysis data, description data, and interpretation data. Results this research find that style language or figure of speech on lyrics song Amazing Love Andmesh album Kamaleng there is 3 language styles. That is, (1) style comparative language which includes hyperbole, and litotes , (2) affirmative language style which includes repetition, and climax, (3) contradictory language style which includes antithesis.